2017
DOI: 10.1053/j.gastro.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Features of Aflatoxin-Associated Hepatocellular Carcinoma

Abstract: We identified specific genetic and mutation features of HCCs associated with aflatoxin exposure, including mutations in ADGRB1, compared to HCCs from general populations. We associated these mutations with increased vascularization and expression of PD-L1 in HCC tissues. These findings might be used to identify patients with HCC due to aflatoxin exposure, and select therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 42 publications
4
97
0
2
Order By: Relevance
“…One of aflatoxins degradation products, the metabolite exo-epoxide, forms a covalent bond with guanyl N7 (AFB1-N7-Gua), ultimately leading to G>T mutations during replication. Consistently, signature 24 has previously been found in a subset of liver cancers (Chawanthayatham et al, 2017;Zhang et al, 2017), but has not been reported for other cancer entities. We therefore tested, if the observed enrichment of signature 24 was solely introduced by a strong mutagenic effect in the liver.…”
Section: Aflatoxin Mutational Signature In Organs Of the Dietary Tractsupporting
confidence: 82%
“…One of aflatoxins degradation products, the metabolite exo-epoxide, forms a covalent bond with guanyl N7 (AFB1-N7-Gua), ultimately leading to G>T mutations during replication. Consistently, signature 24 has previously been found in a subset of liver cancers (Chawanthayatham et al, 2017;Zhang et al, 2017), but has not been reported for other cancer entities. We therefore tested, if the observed enrichment of signature 24 was solely introduced by a strong mutagenic effect in the liver.…”
Section: Aflatoxin Mutational Signature In Organs Of the Dietary Tractsupporting
confidence: 82%
“…Aflatoxins are common contaminates of staple foods and have been found to be carcinogenic in many animal species, including humans . Aflatoxin exposure is clustered in high‐risk regions, where the combination of humid weather and improper food storage conditions expose the majority of the local population to aflatoxins, significantly increasing the incidence of liver cancer . The identification and removal of this risk factor has substantially decreased the incidence of liver cancer in young adults, suggesting the importance of controlling aflatoxin as a preventive measure .…”
Section: Discussionmentioning
confidence: 99%
“…45 Aflatoxin exposure is clustered in high-risk regions, where the combination of humid weather and improper food storage conditions expose the majority of the local population to aflatoxins, significantly increasing the incidence of liver cancer. 9 The identification and removal of this risk factor has substantially decreased the incidence of liver cancer in young adults, suggesting the importance of controlling aflatoxin as a preventive measure. 46 Tobacco smoking remains a severe public health concern in China, despite the implementation of tobacco control policies since the signing of the WHO Framework Convention on Tobacco Control in 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while the current paper was in review, a publication on HCCs from Qidong County, a region of known aflatoxin exposure, extracted a signature similar to COSMIC Signature 24 from HCC somatic mutations (Zhang et al 2017).…”
mentioning
confidence: 99%